STRATEGI OCCUPATIONAL SAFETY AND HEALTH DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. HALEYORA POWER KOTA JAKARTA SELATAN - Kamila Mutiara Khanza; Fathan Arif (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to examine the implementation of Occupational Safety and Health (OSH) strategies and their impact on employee performance at PT. Haleyora Power. The company operates in the field of electricity operation and maintenance services, which involves a relatively high level of occupational risk; therefore, the implementation of OSH is essential. This study employs a qualitative approach with a descriptive method. Data were collected through interviews with the OSH Team Leader, OSH Supervisor, OSH Coordinator, Field Technicians (Yantek), and Administrative Staff, supported by company documentation. The results show that the implementation of the OSH system at PT. Haleyora Power has been carried out properly and in a structured manner, particularly in terms of management policy and commitment. The implementation of OSH has a positive impact on employee performance, as reflected in increased compliance with OSH procedures, work discipline, work quality, and employee productivity. However, several challenges remain in its implementation, including suboptimal employee awareness, limited supervision, work target pressure, and limited OSH supporting facilities. To address these challenges, the company is expected to implemented various strategies, such as strengthening the safety culture, conducting continuous Occupational Safety and Health (OSH) training programs, improving supervision, and integrating OSH into the employee performance appraisal system. Thus, the implementation of Occupational Safety and Health not only functions as an effort to prevent workplace accidents but also plays an important role in improving employee performance in a sustainable manner. Keywords: Occupational Safety and Health, Employee Performance, Workplace Safety